Gynecomastia – evaluation and current treatment options - Johnson RE; Murad MH; Kermott CA (Dove Medical Press, 2011)
Ruth E Johnson, Cindy A Kermott, M Hassan MuradMayo Clinic, Division of Preventive, Occupational and Aerospace Medicine, Rochester, Minnesota, USADate of preparation: 11th January 2011Conflict of Interest: None declaredClinical question: What is the best management approach for gynecomastia?Results: In most patients, surgical correction usually leads to immediate cosmetic and symptomatic improvement and is considered the best approach. In men who are being treated with antiandrogen therapies, pharmacological intervention with tamoxifen is the most effective approach, followed by radiotherapy.Implementation: Pitfalls to avoid when treating gynecomastia - Failure to detect the very rare male breast cancer - Overly aggressive early intervention or evaluation - Appropriate medical intervention - When to refer to specialist treatmentKeywords: gynecomastia, testosterone, estrogen